Pengentasan Self-Harm Pada Siswa SMP Negeri 10 Semarang Dengan Konseling Kelompok Teknik REBT - Aisyah, Nur Siti (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2022)
This study aims to improve students' rational thinking patterns by providing group counseling services with REBT techniques to improve self-control for students at SMP Negeri 10 Semarang. Given how important a rational mindset that students must have in increasing self-control, especially for students in junior high school who have entered or recognized the social world widely so that they will experience various complex problems, it is necessary to strive to build a rational mindset. With this rational emotive behavior therapy group counseling service, it is hoped that it can affect the alleviation of self harm that occurs in students in increasing self-control. This research method is quantitative pre-experimental research design. This research is presented in the form of natural objects, sampling is done using purposive sampling technique, the samples are students of class 8C and class 8H with certain criteria the highest cases, the criteria determined are students who are victims of self-harm with low self-control. There are initial data and final data. The results of the initial data analysis were seen from the pre-test before being given treatment and the results of the final data analysis were seen from the post-test results after being treated using the rational emotive behavior therapy group counseling service. The results of this research are the working hypothesis (Ha): There is an Influence of Group Counseling Services Using REBT Technique on Alleviating Self-Harm in Students of SMPN 10 Semarang, Hypothesis Nil (Ho): There is no Effect of Group Counseling Services Using REBT Technique on Alleviating Self-Harm Harm to Students of SMPN 10 Semarang